Association between NUTRIC score and ICU mortality in patients with sepsis: a prospective cohort study - Xie, Mingjie; Huang, Liuyun; Li, Ling; Qin, Yuanyuan; Feng, Biheng; Cai, Qingjiang; Huang, Debin (Frontiers in Nutrition, 2025)
PurposeThis study aimed to explore the association between the Nutrition Risk in Critical Illness (NUTRIC) score and the risk of ICU mortality in patients with sepsis.MethodsThis was a single-center, prospective cohort study that enrolled septic patients admitted between November 2024 and May 2025 to Wards 1 and 2 of the Department of Critical Care Medicine at the First Affiliated Hospital of Guangxi Medical University. A multivariable logistic regression model was applied to evaluate the association between the NUTRIC score assessed within 24 h of ICU admission and ICU mortality. Restricted cubic spline (RCS) analysis was conducted to model this relationship, and robustness was verified via subgroup analysis. Kaplan–Meier survival curve analysis was used to compare cumulative ICU survival rates among different NUTRIC score groups, with differences between groups tested using the log-rank test.ResultsA total of 245 patients with sepsis were included in the study, and the ICU mortality rate was 17.1% (42/245). Multivariable logistic regression showed a statistically significant association between the NUTRIC score and ICU mortality, with each 1-point increase in the score associated with a 92% increase in risk (OR = 1.92, 95% CI: 1.32–2.80, p = 0.002). RCS analysis indicated a significant linear relationship between the NUTRIC score and ICU mortality risk (P non-linearity = 0.704). Subgroup analysis further demonstrated a positive association across all subgroups (ORs > 1), and did not identify any significant interactions. Kaplan–Meier survival curves showed that patients with high nutritional risk (NUTRICb group) had significantly poorer ICU survival than those with low nutritional risk (NUTRICa group) (log-rank test, p = 0.00024).ConclusionThe NUTRIC score is significantly associated with ICU mortality in patients with sepsis, highlighting its potential utility in early ICU risk stratification. Incorporating the NUTRIC score into ICU assessment protocols may help identify high-risk patients early and guide early nutrition or supportive care, potentially improving clinical outcomes.